Thismia brunneomitra, another new species of Thismia (Thismiaceae) from Ulu Temburong, Brunei Darussalam - Hroneš, Michal; Kobrlová, Lucie; Taraška, Vojtěch; Popelka, Ondřej; Hédl, Radim; Sukri, Rahayu Sukmaria; Metali, Faizah; Dančák, Martin (Phytotaxa, 2015)
A new species of Thismia (Thismiaceae) from northwest Borneo is described and illustrated. Thismia brunneomitra was discovered in 2015 in lowland mixed dipterocarp forest in the Ulu Temburong National Park, Temburong district of Brunei Darussalam. The new species is characterized by brown to blackish flowers with twelve darker vertical stripes on the perianth tube, inner tepal lobes that are connate to form a mitre with three very short processes at the apex, three-toothed apical margin of the connective and large wing-like appendage of the connective. An updated determination key of Thismia species found in Borneo is included.